2022
DOI: 10.3390/ijms23095209
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Intermittent Hypoxia Exposure Alternative to Exercise Alleviates High-Fat-Diet-Induced Obesity and Fatty Liver

Abstract: Obesity often concurs with nonalcoholic fatty liver disease (NAFLD), both of which are detrimental to human health. Thus far, exercise appears to be an effective treatment approach. However, its effects cannot last long and, moreover, it is difficult to achieve for many obese people. Thus, it is necessary to look into alternative remedies. The present study explored a noninvasive, easy, tolerable physical alternative. In our experiment, C57BL/6 mice were fed with a high-fat diet (HFD) to induce overweight/obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Lipid metabolism plays a major role in cell physiology, and its changes, which are part of hypoxic adaptation, remain poorly understood [ 56 , 57 ]. The activity of Na,K-ATPase is regulated by the lipid environment, which is realized through direct protein–lipid interactions and/or by influencing the physical properties of the lipid bilayer [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid metabolism plays a major role in cell physiology, and its changes, which are part of hypoxic adaptation, remain poorly understood [ 56 , 57 ]. The activity of Na,K-ATPase is regulated by the lipid environment, which is realized through direct protein–lipid interactions and/or by influencing the physical properties of the lipid bilayer [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxic induces expression of factors such as UCP1, ADR3 (β3-adrenergic receptor), CPT1A, adipose triglyceride lipase (ATGL), PPARα and PGC1α, and arginase in liver. Moreover, the M2 macrophage marker, CD206 and recombinant PPARγ in liver and and UCP1 in brown fat were upregulated [ 230 ]. In contrast, in ApoE knockout mice, 6.5% hypoxic intervention increased adipose Angptl4 levels, inhibited adiponectin lipase, increased fasting plasma triglyceride and very low-density lipoprotein cholesterol levels and increased the size of atherosclerotic plaques [ 231 ].…”
Section: Exogenous Hypoxic and Obesitymentioning
confidence: 99%
“…The specific mechanism by which hypoxia improves glucose and lipid metabolism remains unclear. Animal studies have shown that the regulatory mechanism of IH on metabolism may be related to hypoxia-induced epinephrine (Luo et al, 2022), ameliorating insulin resistance via the HIF-insulin signaling pathway (Tian et al, 2016) recovery of mitochondrial activity (Trzepizur et al, 2015; Table 2).…”
Section: Intermittent Hypoxia and Abnormal Glucose And Lipid Metaboli...mentioning
confidence: 99%
“…HIFs are the major regulators of the hypoxic transcriptional response, and the O 2 -sensitive prolyl/aspartate hydroxylase (PHDs/FIH) regulates HIF activity in the transition between normoxia and hypoxia conditions (Kaelin and Ratcliffe, 2008). Under various pathological conditions, hypoxia conditioning serves to improve the clinical outcome of the disease by regulating the cellular environment (Taylor and Colgan, 2017), thereby enhancing mitochondrial metabolism, enhancing antioxidant and antiinflammatory capacity, and promoting the repair process to reduce the extent of neurological and vascular damage (Walshe and D'Amore, 2008;Tsai et al, 2013;Qiao et al, 2015;Ryou et al, 2017;Manukhina et al, 2018;Pietrogrande et al, 2019;Ren et al, 2020;Li et al, 2022;Luo et al, 2022). Since the underlying cellular and molecular mechanisms are unclear, more relevant research evidence is needed.…”
Section: Hypoxia and Neurovascular Protectionmentioning
confidence: 99%